PENGARUH PERUBAHAN PENJUALAN, ASSET INTENSITY, PROFITABILITY, SIZE, DAN LEVERAGE TERHADAP COST STICKINESS - Evelyn, Evelyn (Jurnal Muara Ilmu Ekonomi dan Bisnis, 2018)
This study aims to obtain empirical evidence on the effect of changes in sales, asset intensity, profitability, firm size, and debt level to cost stickiness on all companies listed in Indonesia Stock Exchange in period 2012-2016. The number of sample companies used in this study is 150 companies. The results of this study indicate that on the net sales condition increased, the increase of SGA cost is higher than the decrease of SGA cost at the time of net sales decrease, asset intensity have a significant positive effect to cost stickiness, profitability has no significant effect on cost stickiness, firm size has no effect significant to the cost stickiness, and the level of debt has a significant negative effect on the cost stickiness.  Keyword: Cost Stickiness, Asset Intensity, Profitability, Sales changes and SizeThis study aims to obtain empirical evidence on the effect of changes in sales, asset intensity, profitability, firm size, and debt level to cost stickiness on all companies listed in Indonesia Stock Exchange for 2012-2016 period. The number of sample companies used in this study are 150 companies. The result of this study indicates that on the condition of net sales increase, the increase of SGA cost is higher than the decrease of SGA cost at the time of net sales decrease, asset intensity has a significant positive effect on cost stickiness, profitability has no significant effect on cost stickiness, firm size has no significant effect on cost stickiness, and debt level has a significant negative effect on cost stickiness.Keywords: Cost Stickiness, Asset Intensity, Profitability, Sales Changes, Firm Size